Analisis Perbandingan Kinerja Keuangan Bank Syariah Dan Bank Konvensional Yang Listing Pada Bursa Efek Indonesia Periode 2014-2018 (Studi Pada Bank BRI, Tbk dan Bank Mandiri, Tbk yang Listing Pada Bursa Efek Indonesia Periode 2014 – 2018) - Galuh Budi Astuti; Melita Neri Widya Prastiwi (Akubis : Jurnal Akuntansi dan Bisnis, 2023)
This study aims to determine the comparison of the financial performance of Islamic Banks and Conventional Banks represented by Bank Rakyat Indonesia and Bank Mandiri for the period 2014 – 2018. The type of research used is descriptive with a quantitative approach. The population in this study amounted to 4 banking companies. Source of data used in this study is secondary data, and data collection techniques using documentation. Testing was carried out using the Independent Sample T-Test with a significance level of 5%. The results of the analysis show that the financial performance between Islamic Banks and Conventional Banks is seen from the liquidity aspect which is represented by the Loan to Deposit Ratio, the profitability aspect which is represented by Return On Assets, the capital aspect which is represented by the Capital Adequacy Ratio, the credit quality aspect which is represented by Non Performing Loans, and the aspect of efficiency represented by Operating Expenses Operating Income, has a significant difference and shows that Conventional Banks have better financial performance than Islamic Banks.